2017
DOI: 10.21873/anticanres.12163
|View full text |Cite
|
Sign up to set email alerts
|

Pre-surgical Multiparametric Assessment of Breast Lesions Using 3-Tesla Magnetic Resonance

Abstract: Multiparametric 3T-MRI breast imaging shows excellent results in evaluation of breast cancer compared to histological findings, both for primary tumor and nodal metastases. The greatest contribution to improving diagnostic performance is the evaluation of diffusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Elevated levels of tCho have been detected in malignant tumors, including BC, and are determined by the increased cell membrane turnover of neoplastic processes. Several studies have demonstrated that the inclusion of MRS in conventional breast MR examination improves diagnostic accuracy and reduces the number of unnecessary biopsies, since MRS has shown an adequate sensitivity and specificity in distinguishing between benign and malignant lesions [ 18 , 19 , 20 , 21 ]. Recent studies demonstrated that the detection of elevated tCho levels is associated with biological aggressive cancer phenotypes characterized by a high grade, large dimensions and high Ki67 proliferation rate [ 18 , 22 ].…”
mentioning
confidence: 99%
“…Elevated levels of tCho have been detected in malignant tumors, including BC, and are determined by the increased cell membrane turnover of neoplastic processes. Several studies have demonstrated that the inclusion of MRS in conventional breast MR examination improves diagnostic accuracy and reduces the number of unnecessary biopsies, since MRS has shown an adequate sensitivity and specificity in distinguishing between benign and malignant lesions [ 18 , 19 , 20 , 21 ]. Recent studies demonstrated that the detection of elevated tCho levels is associated with biological aggressive cancer phenotypes characterized by a high grade, large dimensions and high Ki67 proliferation rate [ 18 , 22 ].…”
mentioning
confidence: 99%